Analisis SWOT Dalam Menentukan Strategi Pemasaran Pada Sekolah Sepak Bola Al-Hudud Karawang - Sugema Suryadi; Netti Nurlenawati; Dexi Triadinda (STIE AMKOP, 2023)
The position of football in Indonesia has now begun to shift from football as a sport and then turned into a business field, as happened in previous European countries. This position places football into a new industry. The purpose of this research is to identify, analyze and explain internal and external environmental factors as well as positioning and marketing strategies at the Al Hudud Football School Karawang. The population of this study is the entire football school family. Al Hudud Falkirk, numbering 150 people. The sampling technique in this study was non-probability sampling with purposive sampling. The calculation of this research sample used the Lameshow formula. Data collection techniques in this study used direct observation and interview methods. Data analysis techniques in this study used Scale Range analysis and SWOT Analysis. The results showed that Al Hudud Soccer School obtained an IFAS of 1.26 and an EFAS of 1.45. The right marketing strategy for Al Hudud Football School is to maintain the trust of consumers or parents of students by improving the quality of service, providing quality assurance of good coaches to students or parents, expanding marketing through social media and always innovating on the facilities offered. Intensifying promotions in the intended consumer market, improve the quality of business management in order to create solid management and increase cooperation in order to create consumer trust. From the results of the research that has been done, it is hoped that there will be the development of marketing strategy research in football schools and the development of indicators for each variable. For further studies, it is necessary to carry out further research on marketing strategies in a wider soccer school.